The management of depression: the evidence speaks for itself. (March 2023) - Malhi, Gin S.; Bell, Erica; Bassett, Darryl; Boyce, Philip; Bryant, Richard; Hopwood, Malcolm; Lyndon, Bill; Mulder, Roger; Porter, Richard; Singh, Ajeet B.; Murray, Greg
Summary: Comparing the recommendations of two recently published national clinical practice guidelines for depression, this editorial highlights the concordance of advice concerning the selection and sequencing of therapies. Lifestyle and psychological interventions feature prominently and there is broad agreement regarding medication choice and optimisation strategies. The guidelines are therefore a useful resource.